Analisis Determinan Ketimpangan Pendapatan Di Provinsi Jawa Barat Tahun 2015-2020 - widyastuti dias; Lucia Rita Indrawati (Jurnal Ekonomi Pembangunan, 2021)
This study aims to analyze the factors that influence income inequality in the province of West Java. The data used is in the form of a cross-section of 28 districts or cities in the area of West Java and a time series for a period of 6 years, namely from 2015-2020. This study uses panel data regression analysis using a fixed-effect model and is processed with the help of Eviews 10. The results showed that the Human Development Index had a significant positive effect on income inequality. The population had an insignificant negative effect on income inequality. The open unemployment rate had a positive and minor impact on income inequality.